Giant Intracerebral Hydatid Cyst in a Boy - Thapa, Ashish Jung; Tandon, Asheesh; Agrawal, Alok (Nepal Journal of Neuroscience, 2020)
Giant intra-cerebral hydatid cysts are an extremely rare condition caused by the infestation of larvae of Taenia echinococcus (TE). Humans are infected through the feco-oral route by the ingestion of food and milk, contaminated by dog feces containing the ova of parasite or direct contact with dogs. We report a case of a seventeen-year-old boy with giant right temporo-parieto-occipital hydatid cysts (HC). Giant intracerebral hydatid cysts being rare and can at times lead to death, so surgical excision with preoperative consideration and intraoperative rupture prevention is the best management for a better prognosis.